How satellites can support the information requirements of the Polar Code - Aase, JG; Jabour, J (The Yearbook of Polar Law Online, 2016)
In 2000, the International Maritime Organization (IMO) adopted a new requirement for all international and cargo ships exceeding a certain size, and all passenger ships, to carry Automatic Identification System (AIS) transponders capable of providing information about the ship to other ships and to coastal authorities automatically. The requirement became effective for all ships on 31 December 2004. AIS provides other vessels with information about, for example, a ship's identity, position, course, speed and destination. The IMO is finalizing implementation of the Polar Code for the safety of vessels, which will apply in both polar waters and will require additional information about the profile of the fleets of ships operating there. However it must be noted that the AIS data is generally only available from legitimate operators (for example, licensed fishers, tourist operators and vessels on government service) and if the AIS transponder is turned off, the vessel becomes virtually invisible. This methodology, therefore, is not a stand-alone system. Norway has currently two satellites in polar orbit capable of receiving AIS signals. AIS is an excellent tool to track tourist vessels and as such create situational awareness and assist in search and rescue operations in the Arctic. The paper presents findings from three regions in the High Arctic: east of the coast of Greenland, north of Svalbard and surrounding the Russian archipelago of Franz Joseph Land, for the years 2010 to 2014 about maritime activities in these regions with a focus on passenger and fishing vessels. It also suggests other satellite-based means for verifying the AIS data.